CD55 Deficiency, Early-Onset Protein-Losing Enteropathy, and Thrombosis - (:unkn) unknown (MASSACHUSETTS MEDICAL SOC, 2017)
BACKGROUND Studies of monogenic gastrointestinal diseases have revealed molecular pathways critical to gut homeostasis and enabled the development of targeted therapies. METHODS We studied 11 patients with abdominal pain and diarrhea caused by early-onset protein-losing enteropathy with primary intestinal lymphangiectasia, edema due to hypoproteinemia, malabsorption, and less frequently, bowel inflammation, recurrent infections, and angiopathic thromboembolic disease; the disorder followed an autosomal recessive pattern of inheritance. Whole-exome sequencing was performed to identify gene variants. We evaluated the function of CD55 in patients' cells, which we confirmed by means of exogenous induction of expression of CD55. RESULTS We identified homozygous loss-of-function mutations in the gene encoding CD55 (decay-accelerating factor), which lead to loss of protein expression. Patients' T lymphocytes showed increased complement activation causing surface deposition of complement and the generation of soluble C5a. Costimulatory function and cytokine modulation by CD55 were defective. Genetic reconstitution of CD55 or treatment with a complement-inhibitory therapeutic antibody reversed abnormal complement activation. CONCLUSIONS CD55 deficiency with hyperactivation of complement, angiopathic thrombosis, and protein-losing enteropathy (the CHAPLE syndrome) is caused by abnormal complement activation due to biallelic loss-of-function mutations in CD55. (Funded by the National Institute of Allergy and Infectious Diseases and others.)
Keywords: DECAY-ACCELERATING FACTOR; PAROXYSMAL-NOCTURNAL HEMOGLOBINURIA; COMPLEMENT REGULATORY PROTEIN; INFLAMMATORY-BOWEL-DISEASE; HEMOLYTIC-UREMIC SYNDROME; MEMBRANOPROLIFERATIVE GLOMERULONEPHRITIS; CELL RESPONSES; INAB PHENOTYPE; T-CELLS; ACTIVATION